Quantification of SHR0302 in human plasma by UPLC–MS/MS and application to a pharmacokinetic study - Ding, Li‐kun; Chen, Yan; Liu, Mei‐you; Gao, Xiao‐hua; Ren, Dan‐jun; Diao, Qing‐bo; Yang, Lin; Wen, Ai‐dong; Wang, Jing‐wen (Biomedical chromatography, 2022)
SHR0302, as a novel Janus kinase (JAK) inhibitor 1, is used for treatment of rheumatoid arthritis (RA) in humans. A novel and sensitive ultra‐high performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) has been developed and validated for determining the concentration of SHR0302 in human plasma. A precipitation deproteinization method was used for plasma pretreatment with methanol. Detection was carried out on an Agilent 1,260 UPLC coupled with a Triple Quad 4000 mass spectrometer operated in positive multiple reaction monitoring mode, and the analytes were separated on a Synergi Polar‐RP C18 (50 × 2.0 mm, 4 μm, Phenomenex) analytical column with gradient elution of 0.1% formic acid, and 2 mmol/l ammonium acetate in water and 0.1% formic acid and 2 mmol/l ammonium acetate in methanol, The selected ion transitions were m/z 415.2 → 258.2 and m/z 398.2 → 258.2 for SHR0302 and SHR143181 (internal standard), respectively. A full validation, including selectivity, linearity, carryover, precision, accuracy, recovery, matrix effect, dilution integrity and stability, was carried out in human plasma. It was successfully applied to a pharmacokinetic study in Chinese healthy subjects after oral administration of SHR0302 tablet.